Knowledge management case study for Taiyo Yuden - Lau, Kenny Kok Tung. (2004)
In today's fast changing and non-linear business environment the only way to gain competitive advantage is by managing intellectual capital, which is more commonly known as Knowledge management (KM). Many organisations are embracing KM but few of them are able to implement it successfully to see the benefits. Implementation of KM is a strategic process and needs careful target setting and review, to ensure KM helps to achieve organizational vision. In this research is an attempt to assess how well Malaysia Sarawak Taiyo Yuden (MSTY) employees understand their corporate vision which often conveyed from top management.